The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fped.2022.959643
|View full text |Cite
|
Sign up to set email alerts
|

Is adherence to the Mediterranean diet associated with good sleep duration in primary-school children?

Abstract: ObjectiveThe Mediterranean diet (MD) contributes to preventing numerous chronic diseases and has benefits on cognitive development. Adherence to the MD is associated with sleep quality and duration in adults and adolescents, but this association seems to have been little investigated in primary-school children. The aim of this cross-sectional study was to verify whether good sleep duration was associated with adherence to the MD.DesignThe study enrolled a sample of Italian primary school children. Their mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The majority (93%) of children with functional gastrointestinal disorders identify certain foods as the cause of exacerbating gastrointestinal complaints, such as abdominal pain or diarrhea, and other foods as the cause of improving these symptoms ( 48 ). Healthy eating patterns and the Mediterranean diet, known to help reduce the risk of chronic disease, disability, and premature death, are associated with improved cognitive performance and gastrointestinal health in children and adolescents ( 50 ). A study of healthy children and adolescents aged 4–18 years from six Mediterranean countries reported that good compliance to the Mediterranean diet resulted in a significantly lower prevalence of functional gastrointestinal disorders and functional constipation (OR = 0.83, p < 0.001, OR = 0.89, p = 0.008, respectively) ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority (93%) of children with functional gastrointestinal disorders identify certain foods as the cause of exacerbating gastrointestinal complaints, such as abdominal pain or diarrhea, and other foods as the cause of improving these symptoms ( 48 ). Healthy eating patterns and the Mediterranean diet, known to help reduce the risk of chronic disease, disability, and premature death, are associated with improved cognitive performance and gastrointestinal health in children and adolescents ( 50 ). A study of healthy children and adolescents aged 4–18 years from six Mediterranean countries reported that good compliance to the Mediterranean diet resulted in a significantly lower prevalence of functional gastrointestinal disorders and functional constipation (OR = 0.83, p < 0.001, OR = 0.89, p = 0.008, respectively) ( 49 ).…”
Section: Discussionmentioning
confidence: 99%